1977
DOI: 10.1104/pp.59.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Senescence in Carnation (Dianthus caryophyllus) by Ethylene

Abstract: Carnation (Dianthus caryophyllus) flowers were exposed to 2^i/l ethylene and examined at intervals to determine the time course of wilting, decrease in water uptake, and increase in ionic leakage in response to ethylene. A rapid decrease in water uptake was observed about 4 hours after initiating treatment with ethylene. This was followed by wilting (in-rolling of petals) about 2 hours later. Carbon dioxide inhibited the decline in water uptake and wilting and this is typical of most ethylene-induced responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 12 publications
2
60
0
Order By: Relevance
“…1). By the time the climacteric had passed (hour 24), the whole flower had wilted and the ends of the petal had started to fray with onset ofautolysis, a sequence ofevents resembling those seen in carnation and other flowers (1,18). Such a climacteric has often been interpreted as one of the physiological responses to autocatalytic ethylene production (15,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). By the time the climacteric had passed (hour 24), the whole flower had wilted and the ends of the petal had started to fray with onset ofautolysis, a sequence ofevents resembling those seen in carnation and other flowers (1,18). Such a climacteric has often been interpreted as one of the physiological responses to autocatalytic ethylene production (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…By the time the climacteric had passed (hour 24), the whole flower had wilted and the ends of the petal had started to fray with onset ofautolysis, a sequence ofevents resembling those seen in carnation and other flowers (1,18). Such a climacteric has often been interpreted as one of the physiological responses to autocatalytic ethylene production (15,18). But unlike carnation, the daylily flower produces little ethylene during senescence, and its senescence is not affected by ethylene or ethylene inhibitors (16; M. Lay-Yee, personal communication), resembling some leaves in this respect (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the effects of exogenous ethylene on stomatal movements demonstrated differential responses between the examined species (Taylor and Gunderson, 1986; Woodrow et al, 1988; Gunderson and Taylor, 1991; Abeles et al, 1992). Exogenous ethylene is known to increase membrane permeability in petal cells (Mayak et al, 1977; Borochov and Woodson, 1989); however, its impact on cell-to-cell water transport has not been thoroughly examined.Water transport across intact higher plant cell membranes occurs predominantly through water channels (aquaporins; Chrispeels et al, 1997). Aquaporins are located in root cell membranes (Chrispeels and Maurel, 1994) at a high density (Johansson et al, 1998).…”
mentioning
confidence: 99%
“…Several studies on the effects of exogenous ethylene on stomatal movements demonstrated differential responses between the examined species (Taylor and Gunderson, 1986;Woodrow et al, 1988;Gunderson and Taylor, 1991;Abeles et al, 1992). Exogenous ethylene is known to increase membrane permeability in petal cells (Mayak et al, 1977;Borochov and Woodson, 1989); however, its impact on cell-to-cell water transport has not been thoroughly examined.…”
mentioning
confidence: 99%
“…Autocatalysis of ethylene production is a common feature of ripening in climacteric fruits (1,6,9) and some other senescing tissues (11), in which an increased synthesis ofethylene is triggered by exposure to ethylene above a threshold level (1,6). Several reports, however, have demonstrated autoinhibition of ethylene production (12,14,15,20,21).…”
mentioning
confidence: 99%